Effects on Growth and Toxin Production of Exposure of Spores of Clostridium botulinum Type F to Sublethal Doses of Gamma Irradiation - Williams-walls, N. J. (1969)
Spores of the Langeland strain of Clostridium botulinum type F were grown at 30 or 10 C after exposure to 0.0, 0.1, or 0.2 megarad of cesium-137 gamma irradiation. When incubated at 30 C, cultures irradiated at the 0.2-megarad level reached the stationary growth phase 15 hr earlier than the 0.0 or 0.1 megarad-irradiated cultures. This was not the result of earlier or more frequent germination of the irradiated spores, the formation of larger individual cells, filament formation, or cell clumping. It appeared to result from elimination of a lytic phenomenon noted in 0.0 and 0.1 megarad-irradiated cultures after 26 and 29 hr of incubation, respectively, which was followed by a second exponential-growth response 5 hr later in these cultures. The time of toxin appearance in culture supernatant fractions was independent of prior irradiation treatment and occurred after 36 hr of incubation. Toxin release was essentially logarithmic until maximal titers were reached and maximal toxin titers were higher in irradiated than in unirradiated cultures. The higher toxin level was sustained over a period of 23 days of 30 C. Toxin produced in the 30 C cultures could not be trypsin-activated. An incubation temperature of 10 C resulted in no outgrowth of spores subjected to 0.2 megarad of irradiation, although spore germination did occur. At 10 C, outgrowth of the 0.1-megarad culture was faster with slightly higher quantities of a more stable toxin than was seen in the unirradiated control. At 10 C, trypsinization was necessary to demonstrate the toxin present in the cultures.